Governance and Risk Management in Sharia Banks and Financial Performance: Tata Kelola dan Manajemen Risiko di Bank Syariah dan Kinerja Keuangan - Wardatul Jaziroh; Nihlatul Qudus Sukma Nirwana (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The financial performance of Sharia commercial banks is crucial for Indonesia's economic growth. Specific Background: This study explores the impact of Good Corporate Governance (GCG), Internal Audit, and Risk Management on the financial performance of Sharia banks, particularly after the enactment of Law No. 21 of 2008. Knowledge Gap: Existing literature shows mixed results regarding the effects of these governance factors, indicating a need for comprehensive analysis in the context of Sharia banking. Aims: The research aims to assess how GCG, Internal Audit, and Risk Management affect financial performance from 2018 to 2021. Results: Analysis of 44 Sharia banks reveals that while Internal Audit negatively affects performance, GCG and Risk Management have significant positive impacts. Novelty: This study introduces a thorough examination of Risk Management alongside GCG and Internal Audit, enhancing the understanding of their roles in Sharia banking. Implications: Findings highlight the importance of strengthening governance frameworks in Sharia banks to improve financial performance, providing insights for investors and policymakers. Highlights: Good Corporate Governance and Risk Management significantly enhance financial performance in Sharia banks. Internal Audit shows a negative impact on the financial performance, emphasizing the need for effective implementation. The study addresses a gap in literature by examining the interplay of GCG, Internal Audit, and Risk Management in the Sharia banking sector. Keywords: Good Corporate Governance, Internal Audit, Risk Management, Financial Performance, Sharia Banks